2021
DOI: 10.3389/fcell.2021.634697
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Two-mRNA Signature Associated With PD-L1 and Tumor Mutational Burden for Prognosis of Lung Adenocarcinoma

Abstract: Due to biological heterogeneity, lung adenocarcinoma (LUAD) patients with the same stage may exhibit variable responses to immunotherapy and a wide range of outcomes. It is urgent to seek a biomarker that can predict the prognosis and response to immunotherapy in these patients. In this study, we identified two genes (ANLN and ARNTL2) from multiple gene expression data sets, and developed a two-mRNA-based signature that can effectively distinguish high- and low-risk patients and predict patients’ response to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…These findings imply that low ARNTL2 expression ccRCC patients with high PBRM1 mutation rates can achieve more clinical benefits from ICI therapy. Furthermore, recent studies reported that ARNTL2 is correlated with prognosis and immune infiltration of lung adenocarcinoma [ 13 , 14 ]. These studies indicate that ARNTL2 may affect the TIME of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings imply that low ARNTL2 expression ccRCC patients with high PBRM1 mutation rates can achieve more clinical benefits from ICI therapy. Furthermore, recent studies reported that ARNTL2 is correlated with prognosis and immune infiltration of lung adenocarcinoma [ 13 , 14 ]. These studies indicate that ARNTL2 may affect the TIME of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored carcinogenesis roles of ARNTL2 in human malignancies such as breast carcinoma and colorectal adenocarcinoma [ 11 , 12 ]. In addition, recent researches reported that ARNTL2 is correlated with poor survival and immune infiltration level of lung adenocarcinoma [ 13 , 14 ]. However, the potential roles of ARNTL2 in ccRCC have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…( 65 ) have found a positive association between the expression of the transcription factor ARNTL2 (aryl hydrocarbon receptor nuclear translocator-like 2) and the outcome of patients with LUAD. ARNTL2 is a paralog of the circadian transcription factor ARNTL and has recently been discovered to also act as a modifier of immune cell infiltration in malignancies ( 66 68 ). Meanwhile, the Wnt antagonist DKK1 (Dickkopf-1) has been implicated in the modulation of immune cell activities as well as the immunosuppressive microenvironment in cancers and has become a promising target for cancer immunotherapy ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, using TIMER database, we discovered that the copy number of the ARNTL2 was negatively related to the infiltration levels of B cell, CD8 + T cell, macrophage, neutrophil in LUAD. By searching Pubmed, we found that the ARNTL2-related immune process affects several types of diseases, such as LUAD [ 79 , 80 ], pancreatic cancer [ 81 ], type 1 diabetes [ 82 , 83 ]. These findings imply that ARNTL2-induced alteration may affect the tumor immune microenvironment and the progression of LUAD.…”
Section: Discussionmentioning
confidence: 99%